Morphometric analysis of fully ossified clavicle bones in North Indian Population: A Study (Indian Internet Journal of Forensic Medicine and Toxicology, 2023)
The clavicle bone is an essential anatomical structure that plays a crucial role in  shoulder girdle function, as it serves as an attachment site for various muscles  and ligaments. The clavicle bone is also important in forensic medicine, as it is  frequently used for age and sex estimation. The aim of this study is to perform a  morphometric analysis of fully ossified clavicle bones in the North Indian population  and compare our findings with previous studies. The clavicle is considered to be an  important bone when dealing with sex differences in skeletal material. The present  study included 84 fully ossified clavicle bones (42 right-sided and 42 left-sided)  of unknown sex and age. Parameters like maximum length, acromial breadth and  height, and sternal breadth and height of clavicles were studied. All measurements  were taken with the help of a vernier caliper and measured in mm. The maximum  length, height, and width of the sternal end of the clavicle were found to be higher  in the left-sided clavicle, while the height and width of the acromial end of the  clavicles were found to be higher in the right-sided clavicles. These variations  could be due to racial, genetic, or mechanical factors. These findings may be  helpful to orthopedic surgeons involved in the surgical correction procedures of  clavicle fractures.
Keywords: Acromial end; Clavicle; Sternal end; Variations